VALUE PARAMETERS OF THE TRANSFORMATION OF THE MEDIA SPACE - Kotlyarova, Victoria (Revista Inclusiones, 2021)
The media space in the modern information society has been transformed into an important component of its functioning and the intensification of information exchanges. The author uses a set of both general scientific and special methods that provide an axiological analysis of the media space: the sociocultural approach, the modeling method and the value-cultural approach. The author interprets the media space as a dynamic integral system with its own specific features: integrity, dynamism, multi-vector, variability, range of resources, the presence of socionormative prescriptions, conventions and values. Value transformations of the media space occur at several levels, which have their own essential parameters. The level of “fragmentation” is a reflection of the value potential of information through the “filters” of perception and awareness. The level of "technologization" is due to the specifics of the communication channel and its ability to convey the value of information to the addressee. The level of value interpretation of information, conventionally called by us "stereotyping", is associated with the transformation of information under the influence of attitudes, norms, values, stereotypes of public consciousness. The level of "transformation" is associated with the sublimation of the value system. In the future, the author plans to investigate the ambivalence, contradictions of the media space as a socio-cultural phenomenon.